Forced Passages : Imprisoned Radical Intellectuals and the U.S. Prison Regime - Rodriguez, Dylan (Book collections on Project MUSE., 2006)
In Forced Passages, Dylan Rodríguez argues that the cultural production of such imprisoned intellectuals as Mumia Abu-Jamal, Angela Davis, and Leonard Peltier should be understood as a unique social movement. Dylan Rodríguez traces the lineage of radical prison thought since the 1970s, one formed by the logic of state violence and by the endemic racism of the criminal justice system.